2022
DOI: 10.3390/diagnostics12102453
|View full text |Cite
|
Sign up to set email alerts
|

Muscle and Tendon Stiffness of the Lower Limb of Professional Adolescent Soccer Athletes Measured Using Shear Wave Elastography

Abstract: Background: While adolescents have specific risk factors for acute and chronic injury, there is a lack of preventive medicine algorithms for this vulnerable group. Shear wave elastography (SWE) is currently mainly used for assessing muscle and tendon stiffness in adult athletes and can diagnose tissue pathologies such as tendinopathy. The aim was to investigate differences in quadriceps tendon and muscle stiffness between adolescent and adult professional soccer players using SWE and identify lateral imbalance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Furthermore, no significant influence of BMI on tendon stiffness was found, as earlier studies also concluded [24,26,27]. Regular pre-and post-season preventive SWE examinations of the sport-specific exposed tendons in professional athletes may reduce injury risk by detecting early changes in tissue stiffness [9,28].…”
Section: Influence Of Anthropometric Parameters On Achilles Tendon St...mentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, no significant influence of BMI on tendon stiffness was found, as earlier studies also concluded [24,26,27]. Regular pre-and post-season preventive SWE examinations of the sport-specific exposed tendons in professional athletes may reduce injury risk by detecting early changes in tissue stiffness [9,28].…”
Section: Influence Of Anthropometric Parameters On Achilles Tendon St...mentioning
confidence: 89%
“…A total of 65 professional athletes with a mean age of 20.19 years [16][17][18][19][20][21][22][23][24][25][26][27][28][29] were examined. The median BMI was 22.85 kg/m 2 (IQR 19.60-32.38 kg/m 2 ).…”
Section: Athletes' Characteristicsmentioning
confidence: 99%
“…Furthermore, the sporting activity of the test subjects could influence the measurements of striated muscles. Previous data have demonstrated that different sports can impact SWE measurements of various muscles [20][21][22] . However, our study did not focus on comparing the effects of different types of sport on the quadriceps femoris muscle and the autochthonous back muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Regular longitudinal SWE measurements in combination with a standardized sports medical examination once a year and pre- and post-season SWE measurements may help trainers and doctors to adapt training protocols for the individual athlete to prevent chronic tendon and muscle injuries. This is essential in preventive and rehabilitation medicine for professional athletes and adolescent athletes as lateral imbalances are a risk factor for future injuries and can be detected using SWE [ 48 ]. In this context, further studies are still necessary, as well as further standardization of the measurement method of SWE to improve the consistency of SWE measurements and enhance the comparability of SWE studies.…”
Section: Discussionmentioning
confidence: 99%